QUALITY OF LIFE, LEGAL AWARENESS OF EUTHANASIA AND DISABILITY - Paraskeva Mancheva; Gergana Nenova (Peytchinski Publishing, 2022)
Introduction: a central problem in medical practice is the resumption of good quality of life in chronically ill patients with disability. The unresolved health problems of chronically ill patients with disability inevitably lead to increased consumption of health services and create a risk of a euthanistic predisposition. Aim: to study the relation between quality of life and legal awareness of euthanasia in chronically ill patients with disability. Material and methods: Material: The study includes 173 polymorbid patients with disability, evaluated by the Territorial Expert Medical Commission (TEMC) in the Varna region. The research was conducted during the time period of July-December 2021. Methods: sociological methods - individual and group examinations and statistical methods - analysis (χ2), variance analysis, correlation analysis (r), regression analysis (β). Results and discussion: we establish a predominant influence of the "Environment" and "Physical health" domains while assessing the legal awareness of euthanasia in this vulnerable group in society. Pain and low quality of life, determined by the lack of social support, are important factors in deciding on euthanasia. Conclusion: the low quality of life of chronically ill patients with a disability requires more adequate opportunities, ensuring optimal disease management. Bulgarian society suffers a significant insufficiency of palliative/hospice care, which makes legalizing euthanasia at the moment a premature decision.